Correlation of Depressive Disorder among Patients with Diabetes Mellitus Type 2 and its Complications in Al- Nasiriya City/Iraq - Hussain Hlial Wdaa Al-Sayyad (Journal of Global Pharma Technology, 2018)
Background: Diabetes mellitus and depression are so prevalent diseases, when diabetes comorbid depression, it results in insufficient control of blood sugar with severe complications that increase prevalence and severity of depression. Aims of study: To reveal the prevalence of depression among patients with type two diabetes and to Identify the association of depression with complications of diabetes in comparison with non-depressed patients.   Patients and methods: Cross sectional random sample of diabetic patients in AL-Nasiriya diabetic center and AL-Hussein hospital and private clinic at duration of months from May 2017 to April 2018 were exposed for (Zung self-rating depression scale) with supervision of specialist psychiatrist and physician, physical examination and investigations were achieved by senior physician. Results: (51) patients of sample were males (42) patients were female (37.1%) were single, (37.6%) were illetrant and non-employed. most common complications were (ischemic heart disease (39%) cerebral vascular accident (42%), diabetic foot were (25.8). They were treated in different hypoglycemic drug (oral hypoglycemic, insulin and both). Ethic: All patients were given oral consent, their relative also agree to achieve the screening test, physical examination. Conclusion: Diabetes type 2 and its complications were positively correlated to depression with moderate of high severity in comparison with normal patients.Keywords: DT2, Depression, Complication Nasiriya center of diabetes, Iraq, Zung-self ratting scale.